Peran Ketidakpuasan Kerja terhadap Intensi Turnover Karyawan dengan Stabilitas Anchor sebagai Moderator - Vera Ratna Pratiwi; Bagus Riyono (Faculty of Psychology, Universitas Gadjah Mada, 2017)
This study was designed to measure how big the role of job dissatisfaction (job dissatisfaction) to the employee's desire to leave his work (turnover intention) with moderated by the stability of anchors. The method used in this present study is a quantitative method by distributing questionnaire. The questionnaire consists of job dissatisfaction scale, turnover intention scale, and anchor scale to discover anchor stability. Subjects of the study are 267 permanent employees who work in the banking sector. The results of the study indicate that anchor stabilization is not evidenced to influence the relationship between job dissatisfaction and turnover intention. However, anchors such as materials, others and virtues are believed to influence the relationship between job dissatisfaction and employees' turnover intention. The factor of job dissatisfaction which most influences turnover intention in this study is employee dissatisfaction with salary or rewards.